2016
DOI: 10.1177/0748730416657921
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Models of Circadian Disruption Link SRC-2 Function to Hepatic Pathology

Abstract: Circadian rhythmicity is a fundamental process that synchronizes behavioral cues with metabolic homeostasis. Disruption of daily cycles due to jet lag or shift work results in severe physiological consequences including advanced aging, metabolic syndrome, and even cancer. Our understanding of the molecular clock, which is regulated by intricate positive feedforward and negative feedback loops, has expanded to include an important metabolic transcriptional coregulator, Steroid Receptor Coactivator-2 (SRC-2), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 56 publications
0
15
0
1
Order By: Relevance
“…Kettner et al demonstrated that chronic circadian disruption induces NAFLD and spontaneous hepatocarcinogenesis, promotes genome-wide deregulation and metabolic disruption, and activates CAR (NR1I3, constitutive androstane receptor) which drives NAFLD to NASH, fibrosis and HCC progression (78). Chronic circadian disruption in mice had a profound effect on metabolism, what was also observed in humans and circadian disruption with or without steroid receptor Coactivator-2 (SRC-2) ablation showed association with human HCC gene signature (79). The TIMELESS protein has oncogenic function in human HCC as well (80).…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 83%
“…Kettner et al demonstrated that chronic circadian disruption induces NAFLD and spontaneous hepatocarcinogenesis, promotes genome-wide deregulation and metabolic disruption, and activates CAR (NR1I3, constitutive androstane receptor) which drives NAFLD to NASH, fibrosis and HCC progression (78). Chronic circadian disruption in mice had a profound effect on metabolism, what was also observed in humans and circadian disruption with or without steroid receptor Coactivator-2 (SRC-2) ablation showed association with human HCC gene signature (79). The TIMELESS protein has oncogenic function in human HCC as well (80).…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 83%
“…It has been demonstrated that disruption of the circadian system can have significant implications for liver metabolism and the formation of NAFLD. For instance, knockout of genes involved in the clock system, such as in Brain and Muscle Arnt-Like Protein-1 Ϫ/Ϫ , Clock Ϫ/Ϫ , and Steroid Receptor Coactivator-2 Ϫ/Ϫ mice, resulted in significant metabolic defects, including hepatic steatosis (20,51,57). Furthermore, chronic circadian disruption, for 52 wk, has been shown to cause hepatic steatosis (20).…”
Section: G937 Circadian Disruption Of Metabolismmentioning
confidence: 99%
“…For instance, knockout of genes involved in the clock system, such as in Brain and Muscle Arnt-Like Protein-1 Ϫ/Ϫ , Clock Ϫ/Ϫ , and Steroid Receptor Coactivator-2 Ϫ/Ϫ mice, resulted in significant metabolic defects, including hepatic steatosis (20,51,57). Furthermore, chronic circadian disruption, for 52 wk, has been shown to cause hepatic steatosis (20). In the current study, hepatic steatosis was induced in mice exposed to a RL cycle for only 8 wk, suggesting that the consequences of circadian disruption are relatively quick; however, further investigation on the time course of hepatic steatosis is required.…”
Section: G937 Circadian Disruption Of Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…At least 10% of the liver transcriptome demonstrates rhythmic expression, implying that the circadian clock regulates a large set of hepatic genes [35]. It has been demonstrated that chronic circadian disruption promotes weight gain and hepatic lipid storage in mice [36,37]. This may be the reason for weight loss of liver and slight weight gain of body in our mouse model.…”
Section: Discussionmentioning
confidence: 76%